Identifikasi Ketebalan Lapisan Lapuk pada Area Rawan Longsor Menggunakan Metode Seismik Refraksi (Studi Kasus: Desa Kalirejo Kabupaten Kulonprogo) - Muhardi Muhardi; Radhitya Perdhana; Muhammad Reza July Utama; Mitranikasih Laia; Tisar Dewi Pratiwi; Randha Ayu Nurwulandari (Jurnal Teori dan Aplikasi Fisika, 2020)
Abstract. Kalirejo Village, Pengasih District, Kulonprogo Regency, is an area that is prone to landslides. The purpose of this study is to identify the weathering layer thickness, which is one of the triggering factors for landslides. This study was conducted using the seismic refraction method by applying two lines. Line 1 uses 24 geophones, has a distance of 1 meter between geophones, while Line 2 uses 24 geophones, has a distance of 2 meters between geophones. The results showed that the velocity of seismic wave propagation in the weathering layer for Line 1 was 400 m/s, and in the slip surface was 2,300 m/s. The weathering layer thickness on Line 1 is 7.6 - 9.8 meters and the slope is steep so that this location is predicted to have a potential landslide. While the velocity of seismic wave propagation in the weathering layer for Line 2 was 300 m/s, and in the slip surface was 2,200 m/s. The weathering layer thickness on Line 2 is at less than 2 meters, so this location is predicted not to have a landslide potential even though the slope is steep